Scrutinize of X-rays Compton Scattering Through the Classical Hartemann-Kerman Model and Dalitz-like Plots Technique - Nieto-Chaupis, Huber (2022)
In this paper the identification of harmonics of high order due to the interaction of a GeV electron and a super-intense laser pulse with linear polarization is done. For this it is used the technique known as the Dalitz’s plot whose original main purpose is the identification of resonances through the plotting of 2D histograms from events at particles physics colliders. In this manner the Hartemann-Kerman theory is employed. The contour plots have been done with computational methods in the which the laser is represented by a Gaussian profile. Therefore, the zones with more coloration have been interpreted as the resonances of the processes that have turned out to be the emitted photons. This encompasses the quantum mechanics formulation in the which the final state can be composed by the electron and various emitted X-rays photons.